Crystal Structure of the FAD-Containing Ferredoxin-NADP+ Reductase from the Plant Pathogen Xanthomonas axonopodis pv. Citri - Tondo, Maria Laura (2013)
We have solved the structure of ferredoxin-NADP(H) reductase, FPR, from the plant pathogenXanthomonas axonopodispv. citri, responsible for citrus canker, at a resolution of 1.5˚ A. This structure reveals differences in the mobility of specific loops when compared to other FPRs, probably unrelated to the hydride transfer process, which contributes to explaining the structural and functional divergence between the subclass I FPRs. Interactions of the C-terminus of the enzyme with the phosphoadenosine of the cofactor FAD limit its mobility, thus affecting the entrance of nicotinamide into the active site. This structure opens the possibility of rationally designing drugs against theX. axonopodispv. citri phytopathogen.